1997
DOI: 10.1097/00007632-199712150-00004
|View full text |Cite
|
Sign up to set email alerts
|

1997 Volvo Award Winner in Clinical Studies

Abstract: Lumbar posterolateral fusion with pedicle screw fixation increases the operation time, blood loss, and reoperation rate, and leads to a significant risk of nerve injury. The functional outcome improves significantly with high patient satisfaction, with or without instrumentation. No significant differences were observed between the two groups in functional outcome and fusion rate. The only gain in functional outcome from instrumentation was found in the daily activity category in patients with supplementary ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(59 citation statements)
references
References 41 publications
2
48
1
4
Order By: Relevance
“…Standard techniques for pedicle screw placement require extensive tissue dissection to expose entry points and to provide lateral-to-medial orientation for optimal screw trajectory. Open pedicle screw and rod fi xation have been associated with wide paraspinal muscle dissection, extensive blood loss, lengthy hospital stays, and high cost 3 . Mager…”
Section: 2mentioning
confidence: 99%
“…Standard techniques for pedicle screw placement require extensive tissue dissection to expose entry points and to provide lateral-to-medial orientation for optimal screw trajectory. Open pedicle screw and rod fi xation have been associated with wide paraspinal muscle dissection, extensive blood loss, lengthy hospital stays, and high cost 3 . Mager…”
Section: 2mentioning
confidence: 99%
“…In general, randomized trials comparing fusion with bone grafting alone to fusion with pedicle screws have shown no clinical advantage in terms of pain relief or function for those with instrumentation, although instrumentation does slightly increase the rate of solid fusion [3,[25][26][27][28][29]. Thus, it seems likely that any efficacy advantage of instrumentation in terms of clinical outcomes is small.…”
Section: The Choice Of Surgical Proceduresmentioning
confidence: 99%
“…In contrast, with regard to complications, randomized trials show that patients with instrumentation have a substantially higher likelihood of repeat surgery, higher rates of nerve injury, greater blood loss, longer operative time, and a higher rate of overall complications [3,23,29]. Because implants also are expensive, their use may have the net effect of diverting resources from more highly effective clinical services to less effective clinical services.…”
Section: The Choice Of Surgical Proceduresmentioning
confidence: 99%
“…3,4 However, the classical (open) surgical approach with pedicle fixation (short or long segment) involves extensive exposure and dissection, which is generally associated with a high rate of morbidity: high intraoperative blood loss, and significant infection and muscle injury rates. 5,6 Minimally invasive surgery, in particular percutaneous pedicle fixation, has become increasingly popular in spinal surgery.…”
Section: Introductionmentioning
confidence: 99%